C3aR signaling and gliosis in response to neurodevelopmental damage in the cerebellum - Young, Kevin G; Yan, Keqin; Picketts, David J (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Conditional ablation of the Smarca5 gene in mice severely impairs the postnatal growth of the cerebellum and causes an ataxic phenotype. Comparative gene expression studies indicated that complement-related proteins were upregulated in the cerebellum of Smarca5 mutant mice. Complement proteins play critical roles within innate immune signaling pathways and, in the brain, are produced by glial cells under both normal and pathological conditions. The C3 complement protein-derived signaling peptide, C3a, has been implicated in contributing to both tissue damage and repair in conditions such as multiple sclerosis and stroke. Here, we investigated whether C3a receptor (C3aR) signaling promoted damage or repair in the developing cerebellum of Smarca5 mutant mice. Methods Brain and cerebellum lysates from single Smarca5 conditional knockout (Smarca5 cKO) mice, C3aR1 KO mice, or double mutant mice were used for qRT-PCR and immunoblotting to assess the contribution of C3aR to the Smarca5 cKO brain pathology. Immunohistochemistry was used to characterize alterations to astroglia and phagocyte cells in the developing cerebellum of each of the genotypes. Results C3aR signaling was observed to limit gliosis and promote granule neuron survival during postnatal cerebellar development. In Smarca5 cKO mice, disorganized astroglia with increased GFAP expression develops concurrently with cerebellar granule neuron loss and phagocyte invasion over the first 10 days following birth. Potential ligand precursors of C3aR—VGF and C3—were found to have upregulated expression and/or altered processing during this time. Phagocytes (microglia and macrophages) in both the control and Smarca5 mutant mice were the only cells observed to express C3aR. Loss of C3aR in the Smarca5 cKO cerebellum resulted in increased numbers of apoptotic cells and early phagocyte invasion into the external granule cell layer, as well as an exacerbated disorganization of the Bergmann glia. The loss of C3aR expression also attenuated an increase in the expression of the efferocytosis-related protein, MerTK, whose transcript was upregulated ~ 2.5-fold in the Smarca5 mutant cerebellum at P10. Conclusions This data indicates that C3aR can play an important role in limiting astrogliosis and regulating phagocyte phenotypes following developmental cell loss in the brain.